Advancing sales theory with conceptual papers: what's new and what's next?. Issue 1 (2nd January 2022) - Sohi, Ravipreet S.; Haas, Alexander; Davis, Lenita M.
Abstract: We need more theory specific to the sales discipline, and conceptual papers can play a vital role in its development. Conceptual papers can also provide ideas and perspectives that provide the impetus for new research streams in sales. This article calls for a stronger focus on conceptual papers that develop sales-specific theory and frameworks. To facilitate this endeavor, the article presents possible approaches to developing conceptual papers, key points to consider when doing so, and some exemplars that may inspire sales researchers and help them publish impactful conceptual work.